LANGUAGE AND MEANING IN THE TAYUB TRADITION IN TEGALAGUNG VILLAGE TUBAN REGENCY THROUGH A SOCIOSEMIOTIC APPROACH - Pambudi, Archielian Satrio Putro; Hetty Purnamasari; Imron Amrullah (Universitas PGRI Palembang, 2025)
The Tayub tradition in Tegalagung Village, Tuban Regency, is a cultural performance that combines dance, music, and symbolic language reflecting the values and identity of the local community. This study explores how verbal and non-verbal language in Tayub carries social meaning using a sociosemiotic approach. Data were collected through observation and interviews with key cultural actors, including dancers (ledhek), musicians, and elders. The analysis applies Peirce’s semiotic theory and the concept of symbolic interaction to understand how language and signs operate in Tayub performances. Findings show that Tayub functions not only as entertainment but also as a medium of communication, cultural preservation, and social bonding. Verbal elements such as song lyrics and spoken interactions convey messages of love, respect, and tradition, while non-verbal signs like gestures, costumes, and facial expressions carry symbolic meanings that reflect social roles and values. The use of language in Tayub is context-dependent and varies according to the performer, audience, and setting. This study highlights the importance of understanding traditional performances through a linguistic and semiotic lens to preserve their cultural significance and deepen appreciation of local heritage.